Wuluh Starfruit (Averrhoa Bilimbi) Extract Gel For Recurrent Aftosa Stomatitis - Umaimatun Nakhil; Isabella Meliawati Sikumbang; Nugrahani Hendra Putri; Heni Lutfiyati (Jurnal Farmasi Sains dan Praktis, 2019)
The purpose of this study was to test the antibacterial activity of the gel extract of Wuluh starfruit (Averrhoa bilimbi L.). So that it can provide a representation of the use of starfruit in medicine and as an enrichment of insight. Averrhoa bilimbi L contains flavonoids, tannins and saponins which have antibacterial properties. The stages that have been carried out include identification and determination of the starfruit fruit plant, then the simplicia powder of starfruit is extracted using 70% ethanol by maceration which is then carried out evaporation on the waterbath to obtain thick extract. Then made the gel preparation with a concentration of b / v 40%, 45% and 50%. Evaluation of stability physical gel includes organoleptic test, homogeneity, pH, viscosity and spreading ability. The result showed that the three formulas were thick, brown with a characteristics smell of starfruit, homogeny, pH 5, viscosity 190-260 dPas and the spreadability test was 2,5-4,2 cm. Then a bacterial suspension was made by being immersed for 24 hours at 37 ℃. Then tested by dividing into 5 treatment groups, with positive controls Amoxicillin and negative control gel basis. The results showed that the average inhibition zone for each treatment was positive control 4.66 cm, negative control 0 cm, gel 40% 1.77 cm, gel 45% 1.93 cm, and gel 50% 2.67 cm. From the average inhibitory zone it can be seen that gel wuluh starfruit extract has antibacterial activity.